2017
DOI: 10.1111/jfpp.13234
|View full text |Cite
|
Sign up to set email alerts
|

The effects of selected metal ions on the stability of red cabbage anthocyanins and total phenolic compounds subjected to encapsulation process

Abstract: In this study, the stability of red cabbage anthocyanins and total phenolic compounds (TPC) co‐pigmented with various metals ions (Al3+, Ca2+, Fe3+, and Sn2+) under thermal treatment, spray drying, and storage was investigated. In general, it was found that the addition of metal ions accelerated the anthocyanins degradation but delayed TPC loss. Thermally treated samples experienced the highest loss of anthocyanins (k = 0.00173 min−1) when Sn2+ was added whereas less detrimental effect (k = 0.00106 min−1) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…In order to confirm this assumption, the control experiments were conducted by incorporating Fe 3+ and Fe 2+ into ACN, respectively. As shown in Figure S1, it was clearly found that Fe 3+ had an obvious effect on the stability and the color of ACN, which was also consistent with the references [49,50,51]. Therefore, the color phenomenon of ACN/Mt was mainly ascribed to the Fe species in Mt.…”
Section: Resultssupporting
confidence: 86%
“…In order to confirm this assumption, the control experiments were conducted by incorporating Fe 3+ and Fe 2+ into ACN, respectively. As shown in Figure S1, it was clearly found that Fe 3+ had an obvious effect on the stability and the color of ACN, which was also consistent with the references [49,50,51]. Therefore, the color phenomenon of ACN/Mt was mainly ascribed to the Fe species in Mt.…”
Section: Resultssupporting
confidence: 86%
“…The presence of stannous ion results in a lower pH value of dye solution along with reacting with ortho-hydroxyl groups which yield stannous co-pigmentation (Ratanapoompinyo et al , 2017; Sigurdson et al , 2017) and form the purplish and blue color at the strong and mild acidic condition. Cyanidin, Delphinidin and Petunidin are a kind of anthocyanin with two hydroxyl substitutions on their B-ring and can form a metal-anthocyanin complex (Goto, 1989; Takeda, 2006; Castañeda-Ovando et al , 2009; Fedenko et al , 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The results of dyed samples showed that mordanted wool samples caused a blue-greenish and blue color, as well as the associated hue angle, ranged from 213° through 271° (Figure 3). Stannous ion reacts with ortho-hydroxyl groups of anthocyanin compounds (Ratanapoompinyo et al , 2017; Sigurdson et al , 2017) and forms stannous co-pigmentation with a purplish color. According to the applied pH and anthocyanin concentration, this co-pigmentation results in the appearance of various colors on the dyed wool samples which vary from blue to blue-greenish color.…”
Section: Resultsmentioning
confidence: 99%
“…The peroxide value was determined by the official method of American Oil Chemist Society (AOCS, ). The kinetics of quality degradation was described by the first order equation (Ratanapoompinyo et al ., ): CtC0=e-kt, where t was the storage time. C 0 and C t were the quality attributes of the sample at the beginning and at time t , respectively.…”
Section: Methodsmentioning
confidence: 97%